Past connections with the mainland structure patterns of insular species richness in a continental‐shelf archipelago (Aegean Sea, Greece). Issue 10 (29th March 2021) - Hammoud, Cyril; Kougioumoutzis, Konstantinos; Rijsdijk, Kenneth F.; Simaiakis, Stylianos M.; Norder, Sietze J.; Foufopoulos, Johannes; Georgopoulou, Elisavet; Van Loon, Emiel E.
Abstract: Recent research in island biogeography has highlighted the important role of late Quaternary sea‐level fluctuations in shaping biogeographic patterns in insular systems but focused on oceanic systems. Through this study, we aim investigate how late Quaternary sea‐level fluctuations shaped species richness patterns in continental‐shelf island systems. Focusing on the Aegean archipelago, we first compiled maps of the area's geography using published data, under three sea‐level stands: (a) current; (b) median sea‐level over the last nine glacial–interglacial cycles (MSL); and (c) Last Glacial Maximum (LGM). We gathered taxon–island occurrences for multiple chorotypes of angiosperms, butterflies, centipedes, and reptiles. We investigated the impact of present‐day and past geographic settings on chorological groups by analyzing island species–area relationships (ISARs) and using generalized linear mixed models (GLMMs) selection based on multiple metrics of goodness of fit. Our results confirm that the Aegean's geography has changed dramatically since the LGM, whereas the MSL only modestly differs from the present configuration. Apart for centipedes, paleogeographic changes affected both native and endemic species diversity through altering connections between land‐bridge islands and the mainland. On land‐bridge islands, we detected over‐representation of native species and under‐representation of endemics. Unlike oceanic islands, sea‐level‐driven increase of isolation and area contraction did not strongly shape patterns of species richness. Furthermore, the LGM configurations rather than the MSL configuration shaped patterns of endemic species richness. This suggests that even short episodes of increased connectivity with continental populations are sufficient to counteract the genetic differentiation of insular populations. On the other hand, the over‐representation of native nonendemic species on land‐bridge islands reflected MSL rather than LGM mainland connections. Our study shows that in terms of processes affecting species richness patterns, continental archipelagos differ fundamentally from oceanic systems because episodic connections with the mainland have profound effects on the biota of land‐bridge islands. Abstract : In the Aegean archipelago, the shorter lasting configurations of the Late Glacial Maximum promoted increased connectivity with the mainland, thereby counteracting processes promoting endemism. This result contrasts strongly with observations made on oceanic island, where longer lasting configurations largely shaped the current species diversity. This highlights that, in terms of processes affecting species richness patterns, continental archipelagos differ fundamentally from oceanic systems.